Effect of exercise-induced weight control on phospholipid profile and gene expression - Ouyang, Ping (Kansas State University, 2007)
Body weight control via increasing exercise and/or decreasing calorie intake has been linked to a reduced cancer risk in animal models. However, the underlying mechanisms are not clear. This study assessed the impact of exercise with or without limited dietary calorie intake on the overview profiling of phospholipids and gene expression in the skin tissues of weight controlled-mice. Mice were randomly assigned to three groups: ad libitum-fed sedentary control, ad libitum-fed treadmill exercise at 13.4 m/min for 60 min/d, 5 d/wk (Ex+AL), and exercise but pair-fed with the sedentary control (Ex+PF). After 10 wks, Ex+PF but not Ex+AL mice demonstrated a significant decrease in both body weight and percentage of body fat when compared to the sedentary controls. Among 338 phospholipids measured in the skin samples by electrospray ionization mass spectrometry, most classes of phosphatidylinositol (PI), phosphatidylcholine-containing lipids with ether linkage (ePC), and some lysophosphatidylcholine (lysoPC) significantly decreased in Ex+PF mice when compared to the controls. Furthermore, some species of phosphatidylcholine (PC) and phosphatidylethanolamine (PE) containing omega-3 18:0-22:6 fatty acyl combinations increased significantly in Ex+PF mice. A total of 25 significantly-changed phospholipids were distinguishable between diet and exercise treatments by discriminant analysis. The reduced PI in Ex+PF mice was observed concomitantly with a significant reduction of PI3K protein expression. Among the 45,101 probe sets tested in skin tissues, expression of 839 genes was significantly changed by exercise with or without limited dietary calorie intake. The genes with impacted expression were involved in oxidative stress, inflammatory response, lipolysis, protein synthesis, and signaling pathway. Up-regulated expression of genes involved in elongation of long chain fatty acids in Ex+PF but not Ex+AL mice appears to partially account for increased level of 18:0-22:5PC/PE and 18:0-22:6 PC/PE. Taken together, these data indicate that controlling body weight via exercise with limited dietary calorie intake rather than exercise alone significantly modified phospholipid and gene expression profiles. The altered profiles may be associated with cancer preventive mechanisms; in particular, reduced PI and PI-related PI3K expression and altered expression of genes involved in protein kinase activity and lipid metabolism may prevent cancer.
Keywords: Exercise; Cancer prevention; Lipidomics; Gene expression; Health Sciences, Nutrition (0570)